Ozone/Thiosulfate-Assisted Leaching of Cu and Au from Old Flotation Tailings - Stefan Trujić; Miroslav P. Popović; Vesna Conić; Miloš Janošević; Filip Alimpić; Dragoljub Bajić; Ana Milenković-Anđelković; Filip Abramović (Molecules)
The growing demand for metal production promotes the search for alternative sources and novel modalities in metallurgy. Flotation tailings are an important secondary mineral resource; however, they might pose a potential environmental threat due to containing toxic metals. Therefore, proper leaching reagent selection is required. Ozone is an alternative oxidizing agent for metal leaching, as its use prevents contaminating product generation while increasing the noble metal extraction efficiency in the presence of complexing agents. In this study, the feasibility and efficiency of combining the use of thiosulfate and ozone for gold and silver extraction have been investigated as an eco-friendly alternative for recovery from flotation tailings. Two sets of samples from old flotation tailings of Copper Mine Bor (Serbia) were prepared and physico-chemically characterized, then treated in two experimental leaching procedures, followed by thorough XRD and SEM/EDS analyses of the products. It showed that after 1 h of leaching in a water medium at room temperature and a solid-to-liquid phase ratio of 1:4, 88.8% of Cu was obtained, while a high efficiency of Au extraction from solid residue (after Cu leaching) was attained (83.4%). The results suggest that ozone-assisted leaching mediated by Ca-thiosulfate can be an effective eco-friendly treatment for noble metals recovery from sulfide-oxide ores.